(untitled) (The Review of Diabetic Studies, 2025)
Preventive healthcare focuses on addressing health risks proactively before they develop into chronic or acute conditions. This article examines the role of collaborative healthcare teams in promoting and implementing preventive measures. Through teamwork, these teams bridge gaps in education, early detection, and long-term health planning. The research highlights advocacy principles such as communication, patient empowerment, and collaborative decision-making, while also addressing challenges like limited resources and resistance to change. The article concludes with practical recommendations to enhance group involvement in advancing preventive healthcare and building healthier communities.